Translation of English modality into Arabic based on selected United Nations resolutions on Gaza war / Mohammed H. M. Al Aqad - Mohammed H.M., Al Aqad (2015)
Multilingualism is one of the basics for working as translator with the United Nations (UN). The translation of UN documents plays an important political, legal and practical role in the functioning of the Organization. Translating UN documents is considered a crucial issue for translators. The translation of English modals into Arabic in the UN resolutions is a very significant and sensitive issue as these modals play a key role in stopping or continuing the Israeli aggression on Gaza and any mistranslation or misinterpretation of these modals may lead to more fights for many years. Moreover, translating UN documents might raise several serious problems in translation; these problems are due to the different translations of modality and the misinterpretations between the intended meanings of modals with their inherent notions, which could result in a certain amount of ambiguity. This study examines the translation of modal expressions from English into Arabic used in the United Nations resolutions during the war on Gaza from 2008 till 2012. The research corpus is based on 30 UN texts selected of a total from 10 UN resolutions. The study employs Coate's (1983) semantic categorization of modal auxiliaries to identify the English modals and their Arabic equivalents used in the UN resolution texts, and Vinay and Darbelnet's modal of translation techniques (1958/1995) to determine the translation techniques/procedures used by the UN translators in translating English modals into Arabic, and display the differences in meaning reflected in both languages. The findings show that the sentence structure in the Arabic translation is changed. Beside, optional and obligatory transposition is used. However, the overall meaning of the sentence is sustained but the details of the message are different from the original text. Keywords: Legal translation, English and Arabic Modals, UN resolutions, Translation techniques.